Individual stress response patterns: Preliminary findings and possible implications. - Rebecca Jacoby (Public Library of Science (PLoS), 2021)
Background Research on stress occupied a central position during the 20th century. As it became evident that stress responses affect a wide range of negative outcomes, various stress management techniques were developed in attempt to reduce the damages. However, the existing interventions are applied for a range of different stress responses, sometimes unsuccessfully. Objective The aim of this study was to examine whether there are specific clusters of stress responses representing interpersonal variation. In other words, do people have dominant clusters reflecting the different aspects of the known stress responses (physiological, emotional, behavioral, and cognitive)? Methods The researchers derived a measure of stress responses based on previous scales and used it in two studies in order to examine the hypothesis that stress responses can be grouped into dominant patterns according to the type of response. Results The results of Study 1 revealed four distinctive response categories: psychological (emotional and cognitive), physiological gastro, physiological muscular, and behavioral. The results of Study 2 revealed five distinctive response categories: emotional, cognitive, physiological gastro, physiological muscular, and behavioral. Conclusion By taking into consideration each person's stress response profile while planning stress management interventions and then offering them a tailored intervention that reduces the intensity of these responses, it might be possible to prevent further complications resulting in a disease (physical or mental).